(untitled) (Research, Society and Development, 2022)
The COVID-19 pandemic has drastically affected the life of the Brazilian population in the most diverse areas, especially with regard to food. In view of this current health crisis, the theme on Food Insecurity has gained prominence in the field of public health. Defined as a condition in which a given population, a region or country does not have social and economic access to nutritious food, food insecurity was aggravated during the outbreak by the Novo Coronavírus, evidencing the social inequality that still persists in the country, reinforcing the need and importance of strengthening community restaurants as effective public policies to reduce it. The main objective of this study is to analyze the importance of community restaurant to reduce the food insecurity of users during the COVID-19 pandemic. This is a cross-sectional and descriptive research conducted in an administrative region of the Distrito Federal with 100 individuals who attend the community restaurant. Data collection occurred through the application of a form (interview), being a convenience sample. Through the results obtained, it can be seen that 87% of the interviewees were inserted in some degree of Food Insecurity and that the main reason that made the Community Restaurant essential in the food aspect during the pandemic period is due to the same providing quality healthy meals with affordable price (66.7%). In summary, it is noted that the Community Restaurant collaborated in a crucial way to reduce the food insecurity frameworks of its diners through the offer of balanced and affordable meals.